Intention beyond Idealism and Realism - Homayoun Dahaqin; Bijan Abdolkarimi; Mohammad Shokri (Journal of Philosophical Investigations, 2021)
Husserl's departure for the rejecting of the duality (subject and object) inherent in the nature of the Western metaphysical tradition is the transcendental structure of consciousness. Hence the innate foundation of consciousness is intention. The intention is the act of consciousness and practical objectification; That is, by resorting to methodological and Noesis steps, objects from the type of perception can emerge and are included in the consciousness of the mind. Therefore, in addition to sensory intuition, consciousness has the power of intuition of essences. Therefore, consciousness is always associated with its object. In this way, Husserl's methodological axis in phenomenology is the return to objects, and this return is provided by the power of human comprehension and makes the world its intention's object. This article seeks to explain how the phenomenon of the world is made in the realm of consciousness, as well as how the pure subject and advanced mind in the face of the objective world as the only method of understanding and receiving the universe can be an objectifying action.